Ward renovation and PPE use procedures to protect medical staff from COVID-19 infection - Zhengze Lin; Hongmei Shu; Dongping Jiang; Yanlan He; Hongtao Xia; Yong Liu; Nan Xie (Journal of Infection in Developing Countries)
In the early stages of the coronavirus disease 2019 (COVID-19) outbreak in Wuhan, many cross-infections occurred due to the limited number of wards and insufficient medical staff, which could not cope with the large number of patients visiting the hospital. A series of new infection control measures were implemented in our institution and a Wuhan hospital supported by our medical team, mainly including temporarily transforming the general ward into a passage for the staff to enter the infectious ward and standardizing the procedure for the wearing and removal of personal protection equipment (PPE). These measures significantly improved the situation, and no member of our medical staff was infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) during the middle and late stages of the disease epidemic. We hope that these experiences can provide references for medical institutions that may face an outbreak of COVID-19, especially those in underdeveloped countries and regions.